Clinical Decision‐Making and Guideline Alignment Among Brazilian Physical Therapists: Evidence From Standardized Carpal Tunnel Syndrome Vignettes - Luciane Fernanda Rodrigues Martinho Fernandes; Brenda Thaís Alves Cardoso; Darlisson Bueno Paranhos; Vítor Hugo Mendes Castro; Amanda Avelar de Resende; Paula Regina Mendes da Silva Serrão (Journal of Evaluation in Clinical Practice, 2026)
ABSTRACT Background Clinical practice guidelines (CPGs) are intended to support evidence‐based clinical decision‐making. However, the extent to which physical therapists' clinical decisions align with guideline recommendations remains uncertain, particularly in Brazil. Objective To evaluate the alignment of Brazilian physical therapists' clinical decisions with recommendations from CTS clinical practice guidelines and to examine whether general evidence‐based practice (EBP) knowledge, self‐reported guideline use, and condition‐specific guideline knowledge are associated with this alignment. Methods A cross‐sectional study was conducted using an online questionnaire comprising two clinical vignettes representing mild and moderate CTS. Participants selected assessment and treatment strategies, which were scored using a weighted guideline‐alignment system based on the strength of the supporting evidence. Scores were expressed as percentages. Between‐group comparisons were performed using Welch's independent t ‐tests, and effect sizes were estimated using Cohen's d. Results A total of 282 physical therapists were included. Overall alignment with guideline recommendations was low (mean 46.2%, SD 10.7), with similarly low scores for assessment (45.9% ± 14.5) and intervention (46.5% ± 11.7). No significant associations were observed between guideline alignment and any of the investigated variables (all p > 0.05). Effect sizes were uniformly small. All participants selected at least one non‐recommended intervention, and 66.7% selected at least one non‐recommended assessment procedure. Conclusion Clinical decisions made by Brazilian physical therapists showed limited alignment with CTS clinical practice guideline recommendations. General EBP knowledge, self‐reported guideline use, and condition‐specific guideline knowledge were not significantly associated with guideline alignment, and all observed effect sizes were small. These findings suggest that improving guideline implementation requires addressing factors beyond individual knowledge and highlight the importance of behavioural, organizational, and contextual determinants of clinical decision‐making.